IMPLEMENTASI KEBIJAKAN PENETAPAN KAWASAN TERTIB LALULINTAS DI KOTA PALU - G. Wahyu, Ida Bagus Harta (Katalogis, 2013)
This research aimed at describing, analyzing and interpreting the implementation of the orderly trafric area policy in Palu. The method applied in this research was descriptive qualitative. The data were collected through observation, interview and documentation. Editing data, grouping data,interpreting meaning data, Withdrawal of Conclusion and Suggestion by Miles and Huberman (1992). Technic election informan in this research was pursuant to purposive sampling, while informan amount in writing is six informan. The result of research showing communications factor have walked better, this matter visible from Division of duty and fluency in giving to access the information, so that can support the efficacy of policy implementation. If seen resource Factor from inferential research result not yet walked better, this matter visible from facet of medium and which less be adequate and resorce human being which still lower, goodness from facet mount the education and also from experience facet as implementor in supporting or running implementation of stipulating orderly traffic area policy in palu. Disposition factor nor walk better, this matter caused because character of worker characteristic running area to execute the orderly traffic area not yet as according to procedure, this matter visible from field worker, they will run the duty if there are observation tightly or if formed a special team, to the evaluation to execution of stipulating orderly trqffic area policy in palu. Factor Structure Bureaucracy from result research earn the concluded have walk with good, this matter visible, location of job discription, precisely its meaning have as according to membership which diingikan, and also from facet of Standard of Procedure Operational as according to specified order.